2008
DOI: 10.1016/j.jctb.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Packing d-degenerate graphs

Abstract: We study packings of graphs with given maximal degree. We shall prove that the (hitherto unproved) Bollobás-Eldridge-Catlin Conjecture holds in a considerably stronger form if one of the graphs is ddegenerate for d not too large: if d, Δ 1 , Δ 2 1 and n > max{40Δ 1 ln Δ 2 , 40dΔ 2 } then a d-degenerate graph of maximal degree Δ 1 and a graph of order n and maximal degree Δ 2 pack. We use this result to show that, for d fixed and n large enough, one can pack n 1500d 2 arbitrary d-degenerate n-vertex graphs of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…This conjecture has been proved in the case ∆ 1 ≤ 2 by Aigner and Brandt [1] and Alon and Fisher (for sufficiently large n) [2], and in the case when ∆ 1 = 3 and n is huge by Csaba, Shokoufandeh, and Szemerédi [8]. Bollobás, Kostochka and Nakprasit [5] proved a strengthening of the conjecture when G 1 is d-degenerate and d < ∆ 1 /40. Eaton [9] showed that under the given condition, there is a near-packing of degree 1 of G 1 and G 2 , that is, an embedding of the two graphs into a common vertex set such that the maximum degree of the subgraph defined by the edges common to both copies is 1.…”
Section: Introductionmentioning
confidence: 88%
“…This conjecture has been proved in the case ∆ 1 ≤ 2 by Aigner and Brandt [1] and Alon and Fisher (for sufficiently large n) [2], and in the case when ∆ 1 = 3 and n is huge by Csaba, Shokoufandeh, and Szemerédi [8]. Bollobás, Kostochka and Nakprasit [5] proved a strengthening of the conjecture when G 1 is d-degenerate and d < ∆ 1 /40. Eaton [9] showed that under the given condition, there is a near-packing of degree 1 of G 1 and G 2 , that is, an embedding of the two graphs into a common vertex set such that the maximum degree of the subgraph defined by the edges common to both copies is 1.…”
Section: Introductionmentioning
confidence: 88%
“…Aigner and Brandt [1] and independently (for huge n) Alon and Fisher [2] settled the conjecture in the case ∆ 1 ≤ 2 (this particular case was conjectured by Sauer and Spencer [68]). Csaba, Shokoufandeh, and Szemerédi [21] proved the BECconjecture for ∆ 1 = 3 and huge n. Bollobás, Kostochka and Nakprasit [12] showed that although the BEC-conjecture is sharp, if one of the two graphs is sparse, to be precise, d-degenerate for a small d, then much weaker conditions on ∆ 1 and ∆ 2 imply the existence of a packing. Recall that a graph G is d-degenerate if every subgraph G of G has a vertex of degree (in G ) at most d. In this case, the vertices of G can be ordered so that each vertex has fewer than col(G) := d + 1 neighbors that precede it.…”
Section: Theorem 24mentioning
confidence: 99%
“…Recall that a graph G is d-degenerate if every subgraph G of G has a vertex of degree (in G ) at most d. In this case, the vertices of G can be ordered so that each vertex has fewer than col(G) := d + 1 neighbors that precede it. Theorem 2.10 (Bollobás, Kostochka and Nakprasit [12]) Let d ≥ 2. Let G 1 be a d-degenerate graph of order n and maximum degree ∆ 1 and G 2 be a graph of order n and maximum degree at most ∆ 2 .…”
Section: Theorem 24mentioning
confidence: 99%
See 1 more Smart Citation
“…al use the method of random separation to obtain fixedparameter tractable algorithms for the problem of finding induced cycles and trees in degenerate graphs [5]. Degenerate graphs have also been studied from a theoretical point of view [6,14,4].…”
Section: Introductionmentioning
confidence: 99%